Multiple hashes of single key with passcode for multiple accounts - Lee, Kok-wah; Ewe, Hong-tat (ZHEJIANG UNIV, EDITORIAL BOARD, 2007)
A human's e-life needs multiple offline and online accounts. It is a balance between usability and security to set keys or passwords for these multiple accounts. Password reuse has to be avoided due to the domino effect of malicious administrators and crackers. However, human memorability constrains the number of keys. Single sign-on server, key hashing, key strengthening and petname system are used in the prior arts to use only one key for multiple online accounts. The unique site keys are derived from the common master secret and specific domain name. These methods cannot be applied to offline accounts such as file encryption. We invent a new method and system applicable to offline and online accounts. It does not depend on HTTP server and domain name, but numeric 4-digit passcode, key hashing, key strengthening and hash truncation. Domain name is only needed to resist spoofing and phishing attacks of online accounts.